PENILAIAN AUTENTIK MATA PELAJARAN MATEMATIKA KURIKULUM 2013 GURU KELAS IV KOTA SEMARANG - Apriliana Purwandari, Fajar Cahyadi, (MALIH PEDDAS, 2014)
The change of KTSP curriculum into 2013 curriculumÂ  lead to changes in the assessment system. With the change in valuation system, teachers should be able to adapt and develop appropriate assessment with the curriculum has changed. In this 2013 curriculum using authentic assessment system that can assess the competence of the three domains, namely the domain of attitudes, knowledge, and skills. The problems revealed in this study are Is authentic assessment instrument in the subjects of mathematics which has been prepared by the teacher in accordance with the characteristics of the curriculum in 2013? Goals to be achieved in this study was to determine the suitability of authentic assessment instrument in the subjects of mathematics that had been developed by teachers with the characteristics of curriculum assessment in 2013, this is a type of qualitative research that uses qualitative descriptive approach. The population in this study is a Primary School in Hyderabad who have applied in the process of learning curriculum was radically 2013, amounting to 12 elementary schools. Samples taken are 5 elementary schools in Semarang by using purposive sampling technique. The data in this study was obtained through the analysis of the research instruments and text data card interview. Based on the analysis of experimental data showed that the instrument of authentic assessment in mathematics is organized by fourth grade teachers from five elementary schools in Semarang 85.2% in accordance with the characteristics of curriculum assessment in 2013, where the authentic assessment instruments assessment covers the realm of attitudes, knowledge, and skills. Therefore it can be concluded that the teacher has been able to make an authentic assessment instrument based on the characteristics of the curriculum in 2013.